Effect of Reaction Parameters on the Lipase-Catalyzed Kinetic Resolution of (RS)-Metoprolol - Mariani Rajin; Asiah Zulkifli; Sariah Abang; S.M Anissuzzaman; Azlina Harun Kamaruddin (2020)
Racemic metoprolol is a selective ß1-blocker, which is used in cardiovascular disease treatment. It has been found that (S)-metoprolol has a higher affinity to bind the ß-adrenergic receptor compared to (R)-metoprolol. Moreover, the regulatory authorities’ high market demand and guidelines have increased the preference for single enantiomer drugs. In this work, the lipase-catalyzed kinetic resolution of racemic metoprolol was performed to obtain the desired enantiomer. The type of lipase, acyl donor, and solvent were screened out. This was achieved by Candida antarctica B lipasecatalyzed transesterification of racemic metoprolol in hexane and vinyl acetate as the solvent and an acyl donor, which gave maximum conversion of (S)-metoprolol (XS) of 52%, enantiomeric excess of substrate, (ees) of 92% and product (eeP) of 90% with enantiomeric ratio (E) of 62. This method can be considered as green chemistry, which can be applied to produce other enantiopure beta-blockers.